Method for recycling used foundry sand
Patent Information
- Application Number
- CN202611332623.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-23
AI Technical Summary
国内铸造废砂的重复利用率低于15%,其砂直接排放不但造成资源的浪费,而且其内部成分复杂,废砂固废的直接填埋或排放会产生垃圾渗水,进一步污染水体、土壤、农作物、河流及地下水等,对环境产生极大的危害
(1)本发明的再生砂表面负载有甘露醇,其作为一种多羟基化合物,分子结构中含有丰富的羟基,为后续覆膜时的树脂粘结提供了更多的活性位点,从而显著增强了砂粒与树脂之间的界面结合力,直接提升了材料的常温及高温抗弯强度,并保证高温热稳定性和结构稳定性。
Smart Images

Figure CN122955863A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of foundry waste sand recycling technology, specifically relating to a method for recycling waste foundry sand. Background Technology
[0002] Casting is the foundation of manufacturing, and economic development is inseparable from castings. Sand casting is widely used in the current casting industry because of its low cost, high production efficiency, and simple equipment and processes. However, the reuse rate of foundry waste sand in China is less than 15%. Direct discharge of this sand not only wastes resources, but its complex composition also leads to leachate pollution, further polluting water bodies, soil, crops, rivers, and groundwater, causing significant environmental damage.
[0003] The technology of waste foundry sand recycling uses heating and physicochemical methods to remove impurities such as the binder inert film and harmful particulate dust on the surface of sand particles, so that the waste foundry sand is restored to be close to the original sand and can be used for molding again, thus achieving the purpose of recycling waste foundry sand and completely solving the problem of waste sand treatment. The main methods of waste foundry sand recycling include: (1) dry recycling, after removing metal impurities by crushing and magnetic separation, mechanical grinding or high-speed airflow impact is used to make the sand particles rub against each other to remove the surface binder film; (2) wet recycling, using water emulsion to gently scrub the waste sand, which is suitable for old sand where the binder film can be dissolved in water; (3) thermal recycling, by sending the waste sand into a roasting furnace for high-temperature heating to burn off the organic matter and some clay on the surface of the sand particles, so as to achieve the purpose of recycling.
[0004] Therefore, there is an urgent need for a waste foundry sand recycling method that uses waste phenolic resin foundry sand as raw material, and prepares high-performance coated foundry sand with good flexural strength and heat resistance through high-temperature activation and phenolic epoxy resin coating treatment, thereby realizing the recycling of waste foundry sand. Summary of the Invention
[0005] To address the shortcomings of existing technologies, the present invention aims to provide a method for the recycling of waste foundry sand. This invention first activates waste phenolic resin foundry sand to obtain carbon-containing calcined sand, then impregnates the carbon-containing calcined sand to obtain recycled sand. Simultaneously, plant-based phenolic resin is prepared using guaiacol and formaldehyde as raw materials, and borosilicate-modified plant-based phenolic epoxy resin is obtained through epoxidation and modification treatments. Finally, the recycled sand, borosilicate-modified plant-based phenolic epoxy resin, polyamide curing agent, accelerator, magnesium stearate, and coupling agent are mixed to obtain coated recycled sand for casting. This invention ensures good flexural properties of the material while effectively reducing loss on ignition, thus realizing the recycling of waste foundry sand.
[0006] The technical solution adopted by the present invention to solve the above-mentioned technical problems is as follows: In a first aspect, the present invention provides a method for recycling waste foundry sand, comprising the following steps: S1. First, the waste phenolic resin casting sand is activated to obtain carbon-containing calcined sand, and then the carbon-containing calcined sand is impregnated to obtain recycled sand. S2. Stir and mix the recycled sand and phenolic epoxy resin described in step S1, then add polyamide curing agent, accelerator, magnesium stearate and coupling agent, heat and stir, cool, crush and sieve to obtain coated recycled sand for casting.
[0007] As a preferred technical solution of the present invention, the heating and stirring conditions are as follows: first stirring at 100~110℃ for 60~80min, and then stirring at 115~125℃ for 100~120min.
[0008] As a preferred technical solution of the present invention, each component in step S2 includes, by weight: 80-90 parts of recycled sand, 8-12 parts of phenolic epoxy resin, 4-6 parts of polyamide curing agent, 1-2 parts of accelerator, 1-2 parts of magnesium stearate, and 1-2 parts of coupling agent.
[0009] As a preferred embodiment of the present invention, the weight fraction of the recycled sand can be 80 parts, 82 parts, 84 parts, 86 parts, 88 parts, or 90 parts, etc.
[0010] As a preferred embodiment of the present invention, the phenolic epoxy resin may be in the following weight proportions: 8 parts, 9 parts, 10 parts, 11 parts, or 12 parts, etc.
[0011] As a preferred embodiment of the present invention, the polyamide curing agent may be present in 4, 5, or 6 parts by weight, etc.
[0012] As a preferred embodiment of the present invention, the weight parts of the accelerator may be 1.0 parts, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, or 2.0 parts, etc.
[0013] As a preferred embodiment of the present invention, the magnesium stearate may be in the following weight proportions: 1.0 parts, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, or 2.0 parts.
[0014] As a preferred embodiment of the present invention, the coupling agent may be present in weight parts of 1.0, 1.2, 1.4, 1.6, 1.8, or 2.0 parts, etc.
[0015] As a preferred technical solution of the present invention, the activation treatment step in step S1 is as follows: placing the waste phenolic resin casting sand in a vertical activation furnace, controlling the water vapor flow rate to be 10~20mL / min, and activating it at 840~860℃ for 120~140min to obtain carbon-containing calcined sand.
[0016] As a preferred technical solution of the present invention, the impregnation treatment step S1 is as follows: by weight, 80-90 parts of carbon-containing calcined sand are impregnated in 900-1000 parts of 1mol / L mannitol aqueous solution, impregnated at 30-40℃ for 20-24 hours, filtered, washed with water, and dried to obtain regenerated sand.
[0017] The regenerated sand of this invention is prepared by first placing waste phenolic resin casting sand in a vertical activation furnace for activation treatment. The phenolic resin on the surface of the waste sand is pyrolyzed at high temperature, and water vapor reacts with residual carbon to remove stubborn residual carbon, thereby obtaining calcined sand with a small amount of activated carbon layer on the surface. Subsequently, mannitol is adsorbed and loaded onto the carbon layer surface through hydrogen bonding, serving as a coupling layer for subsequent secondary coating.
[0018] As a preferred embodiment of the present invention, the phenolic epoxy resin is a borosilicate modified plant-based phenolic epoxy resin. The preparation method of the borosilicate-modified plant-based phenolic epoxy resin is as follows: first, plant-based phenolic resin is prepared using guaiacol and formaldehyde as raw materials; then, the plant-based phenolic resin is epoxidized using epichlorohydrin to obtain plant-based phenolic epoxy resin; finally, the plant-based phenolic epoxy resin is modified using borosilicate compounds to obtain borosilicate-modified plant-based phenolic epoxy resin.
[0019] This invention first involves mixing guaiacol and formaldehyde solution to synthesize plant-based phenolic resin. Then, under alkaline conditions and with the catalyst benzyltriethylammonium chloride, the plant-based phenolic resin undergoes an etherification reaction with epichlorohydrin to form a plant-based phenolic epoxy resin. Simultaneously, a borosilicate compound is prepared by sol-gel co-hydrolysis condensation of organosilicon and boric acid. Finally, under the catalysis of dibutyltin dilaurate, the plant-based phenolic epoxy resin and the borosilicate compound undergo hybridization modification to obtain a borosilicate-modified plant-based phenolic epoxy resin.
[0020] As a preferred technical solution of the present invention, the preparation steps of the plant-based phenolic resin are as follows: by weight, 120-130 parts of guaiacol and 62-68 parts of 37% formaldehyde solution are added to a reaction vessel, then 4-6 parts of 40% hydrochloric acid are added dropwise and stirred for 20-30 minutes, the temperature is raised to 70-80℃ and reacted for 8-10 hours, the mixture is allowed to stand and separate into layers, the lower oily liquid is collected and washed with deionized water, and then rotary evaporated to obtain the plant-based phenolic resin.
[0021] As a preferred technical solution of the present invention, the preparation steps of the plant-based phenolic epoxy resin are as follows: by weight, 8-12 parts of plant-based phenolic resin and 90-100 parts of epichlorohydrin are added to a reaction vessel under a nitrogen atmosphere and stirred for 50-60 minutes. Then, 1-2 parts of benzyltriethylammonium chloride are added and reacted at 65-70°C for 3-5 hours. Then, 8-10 parts of 40% sodium hydroxide aqueous solution are added and reacted at 75-80°C for 60-80 minutes. After the reaction is completed, the mixture is filtered, the filtrate is collected and extracted, the lower oily liquid is separated, and the mixture is rotary evaporated to obtain the plant-based phenolic epoxy resin.
[0022] As a preferred embodiment of the present invention, the modification treatment steps are as follows: by weight, 40-45 parts of anhydrous ethanol and 5-10 parts of deionized water are mixed in a reaction vessel, and then 1-2 parts of 3-aminopropyltriethoxysilane are added and stirred at 60°C for 150-250 min. Then, 10-20 parts of borosilicate compound are added and stirred for 30-40 min. Then, 30-40 parts of plant-based phenolic epoxy resin are added and stirred for 50-60 min. After heating to 90°C, 0.4-0.6 parts of dibutyltin dilaurate are added for modification treatment for 6-8 h. After cooling to room temperature, the resin is washed with water and dried to obtain borosilicate modified plant-based phenolic epoxy resin.
[0023] As a preferred embodiment of the present invention, the preparation steps of the borosilicate compound are as follows: by weight, 40-50 parts of phenyltriethoxysilane, 10-12 parts of dimethyldiethoxysilane and 2-4 parts of boric acid are added to 80-90 parts of anhydrous ethanol, then 1-2 parts of 1mol / L hydrochloric acid solution are added and the mixture is heated to 60-70°C and stirred for 100-120 min, rotary evaporated, washed with water and dried to obtain the borosilicate compound.
[0024] As a preferred embodiment of the present invention, the accelerator is selected from one or more of N,N-dimethylbenzylamine, 2-methylimidazole, and 2-ethyl-4-methylimidazole.
[0025] As a preferred embodiment of the present invention, the coupling agent is selected from one or more of silane coupling agent KH-560, silane coupling agent KH-561, and silane coupling agent KH-562.
[0026] Compared with the prior art, the present invention has the following beneficial effects: (1) The surface of the recycled sand of the present invention is loaded with mannitol, which is a polyhydroxy compound with abundant hydroxyl groups in its molecular structure. This provides more active sites for resin bonding during subsequent coating, thereby significantly enhancing the interfacial bonding force between sand particles and resin, directly improving the room temperature and high temperature flexural strength of the material, and ensuring high temperature thermal stability and structural stability.
[0027] (2) The surface of the recycled sand of the present invention is coated with high-performance borosilicate modified plant-based phenolic epoxy resin. The borosilicate modified plant-based phenolic epoxy resin forms BO bonds through the introduction of boron. Its high bond energy and thermal stability significantly improve the heat resistance of the resin at high temperatures. The introduction of silicon can improve the interfacial compatibility between the resin and inorganic sand particles and enhance thermal stability by forming Si-O. At the same time, the uniform carbon thin layer on the surface of the recycled sand has an elastic buffering effect, while the flexible long chain of the coated plant-based phenolic epoxy reduces the brittleness of the resin and synergistically enhances the bending deformation resistance. Attached Figure Description
[0028] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0029] Figure 1 The images show the FTIR spectra of the borosilicate-modified plant-based phenolic epoxy resin, plant-based phenolic epoxy resin, and plant-based phenolic resin in Example 1. Detailed Implementation
[0030] To facilitate understanding of the present invention, the following embodiments are provided. Those skilled in the art should understand that these embodiments are merely illustrative and should not be construed as limiting the scope of the invention.
[0031] The sources of some components in the examples and comparative examples are as follows: Waste phenolic resin foundry sand originated from Chengde Dongwei New Material Technology Co., Ltd. Mannitol, CAS No. 69-65-8, purchased from Sinopharm Chemical Reagent Co., Ltd. Guaiacol, CAS No. 90-05-1, purchased from Sinopharm Chemical Reagent Co., Ltd. Formaldehyde solution, product number F754240, mass fraction 37%, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. Epichlorohydrin, CAS No. 106-89-8, was purchased from Sinopharm Chemical Reagent Co., Ltd. Benzyltriethylammonium chloride, CAS No. 56-37-1, was purchased from Sinopharm Chemical Reagent Co., Ltd. Phenylacetoxysilane, CAS No. 780-69-8, was purchased from Shanghai Maclean Biochemical Technology Co., Ltd. Dimethyldiethoxysilane, CAS No. 78-62-6, was purchased from Shanghai Maclean Biochemical Technology Co., Ltd. Boric acid, CAS No. 10043-35-3, was purchased from Sinopharm Chemical Reagent Co., Ltd. 3-Aminopropyltriethoxysilane, CAS No. 919-30-2, was purchased from Shanghai Maclean Biochemical Technology Co., Ltd. Ordinary phenolic epoxy resin, model F-51, purchased from Jiangsu Sanmu Group Co., Ltd. Polyamide curing agent, brand name PAG200, purchased from Changzhou Yijia New Material Technology Co., Ltd. N,N-Dimethylbenzylamine, CAS No. 103-83-3, was purchased from Sinopharm Chemical Reagent Co., Ltd. 2-Methylimidazole, CAS No. 693-98-1, was purchased from Shanghai Maclean Biochemical Technology Co., Ltd. 2-Ethyl-4-methylimidazole, CAS No. 6227-74-1, was purchased from Shanghai Maclean Biochemical Technology Co., Ltd. Magnesium stearate, CAS No. 557-04-0, was purchased from Shanghai Maclean Biochemical Technology Co., Ltd. Silane coupling agent KH-560 was purchased from Nanjing Jingtianwei Chemical Co., Ltd. Silane coupling agent KH-561 was purchased from Nanjing Jingtianwei Chemical Co., Ltd. Silane coupling agent KH-562 was purchased from Nanjing Jingtianwei Chemical Co., Ltd. Example
[0032] This embodiment provides a method for recycling waste foundry sand, including the following steps: S1. First, place the waste phenolic resin casting sand in a vertical activation furnace, control the steam flow rate to 20 mL / min, and activate it at 860℃ for 120 min to obtain carbon-containing calcined sand. By weight, 90 parts of carbon-containing calcined sand are immersed in 1000 parts of 1 mol / L mannitol aqueous solution and soaked at 40℃ for 20 h. After filtration, washing with water, and drying, regenerated sand is obtained.
[0033] S2. By weight, 90 parts of recycled sand and 12 parts of borosilicate modified plant-based phenolic epoxy resin are mixed together. Then, 6 parts of polyamide curing agent, 2 parts of accelerator N,N-dimethylbenzylamine, 2 parts of magnesium stearate, and 2 parts of silane coupling agent KH-560 are added and the mixture is heated and stirred. First, it is stirred at 110°C for 60 minutes, and then at 125°C for 100 minutes. After cooling, it is crushed and sieved to obtain coated recycled sand for casting.
[0034] Preparation of the borosilicate-modified plant-based phenolic epoxy resin: 130 parts by weight of guaiacol and 68 parts by weight of 37% formaldehyde solution were added to a reaction vessel, followed by the dropwise addition of 6 parts by weight of 40% hydrochloric acid and stirring for 30 minutes. The mixture was then heated to 80°C and reacted for 8 hours. After standing and separating into layers, the lower oily liquid was collected and washed with deionized water, followed by rotary evaporation to obtain the plant-based phenolic resin. Under a nitrogen atmosphere, 12 parts by weight of the plant-based phenolic resin and 100 parts by weight of epichlorohydrin were added to a reaction vessel and stirred for 60 minutes. Then, 2 parts by weight of benzyltriethylammonium chloride were added and reacted at 70°C for 3 hours. Next, 10 parts by weight of 40% sodium hydroxide aqueous solution were added and reacted at 80°C for 60 minutes. After the reaction was complete, the mixture was filtered, the filtrate was collected and extracted, the lower oily liquid was separated, and the mixture was rotary evaporated. Plant-based phenolic epoxy resin was obtained. 50 parts of phenyltriethoxysilane, 12 parts of dimethyldiethoxysilane, and 4 parts of boric acid were added to 90 parts of anhydrous ethanol. Then, 2 parts of 1 mol / L hydrochloric acid solution were added, and the mixture was heated to 70℃ and stirred for 100 min. The mixture was then rotary evaporated, washed with water, and dried to obtain a borosilicate compound. In a reaction vessel, 45 parts of anhydrous ethanol and 5 parts of deionized water were mixed, and 2 parts of 3-aminopropyltriethoxysilane were added and stirred at 60℃ for 250 min. Then, 20 parts of the borosilicate compound were added and stirred for 40 min. Next, 40 parts of plant-based phenolic epoxy resin were added and stirred for 60 min. The mixture was heated to 90℃, and 0.6 parts of dibutyltin dilaurate were added for modification treatment for 6 h. The mixture was cooled to room temperature, washed with water, and dried to obtain a borosilicate-modified plant-based phenolic epoxy resin. Example
[0035] This embodiment provides a method for recycling waste foundry sand, including the following steps: S1. First, place the waste phenolic resin casting sand in a vertical activation furnace, control the steam flow rate to 10 mL / min, and activate it at 840℃ for 140 min to obtain carbon-containing calcined sand. By weight, 80 parts of carbon-containing calcined sand are immersed in 900 parts of 1 mol / L mannitol aqueous solution and soaked at 30℃ for 24 h. After filtration, washing with water, and drying, regenerated sand is obtained.
[0036] S2. By weight, 80 parts of recycled sand and 8 parts of borosilicate modified plant-based phenolic epoxy resin are mixed together. Then, 4 parts of polyamide curing agent, 1 part of accelerator 2-methylimidazole, 1 part of magnesium stearate, and 1 part of silane coupling agent KH-561 are added and the mixture is heated and stirred. First, it is stirred at 100℃ for 80 minutes, and then at 115℃ for 120 minutes. After cooling, it is crushed and sieved to obtain coated recycled sand for casting.
[0037] Preparation of the borosilicate-modified plant-based phenolic epoxy resin: 120 parts by weight of guaiacol and 62 parts by weight of 37% formaldehyde solution were added to a reaction vessel, followed by the dropwise addition of 4 parts by weight of 40% hydrochloric acid and stirring for 20 minutes. The mixture was then heated to 70°C and reacted for 10 hours. After standing and separating into layers, the lower oily liquid was collected and washed with deionized water, followed by rotary evaporation to obtain the plant-based phenolic resin. Under a nitrogen atmosphere, 8 parts by weight of the plant-based phenolic resin and 90 parts by weight of epichlorohydrin were added to a reaction vessel and stirred for 50 minutes. Then, 1 part by weight of benzyltriethylammonium chloride was added and reacted at 65°C for 5 hours. Next, 8 parts by weight of 40% sodium hydroxide aqueous solution were added and reacted at 75°C for 80 minutes. After the reaction was complete, the mixture was filtered, the filtrate was collected and extracted, the lower oily liquid was separated, and then rotary evaporated. Plant-based phenolic epoxy resin was obtained. 40 parts of phenyltriethoxysilane, 10 parts of dimethyldiethoxysilane, and 2 parts of boric acid were added to 80 parts of anhydrous ethanol. Then, 1 part of 1 mol / L hydrochloric acid solution was added, and the mixture was heated to 60℃ and stirred for 120 min. The mixture was then rotary evaporated, washed with water, and dried to obtain a borosilicate compound. In a reaction vessel, 40 parts of anhydrous ethanol and 10 parts of deionized water were mixed, and 1 part of 3-aminopropyltriethoxysilane was added and stirred at 60℃ for 150 min. Then, 10 parts of the borosilicate compound were added and stirred for 30 min. Next, 30 parts of plant-based phenolic epoxy resin were added and stirred for 50 min. The mixture was heated to 90℃, and 0.4 parts of dibutyltin dilaurate were added for modification treatment for 8 h. The mixture was cooled to room temperature, washed with water, and dried to obtain borosilicate-modified plant-based phenolic epoxy resin. Example
[0038] This embodiment provides a method for recycling waste foundry sand, including the following steps: S1. First, place the waste phenolic resin casting sand in a vertical activation furnace, control the steam flow rate to 15 mL / min, and activate it at 850℃ for 130 min to obtain carbon-containing calcined sand; by weight, 85 parts of carbon-containing calcined sand are immersed in 960 parts of 1 mol / L mannitol aqueous solution and soaked at 38℃ for 21 h, filtered, washed with water, and dried to obtain regenerated sand.
[0039] S2. By weight, 84 parts of recycled sand and 9 parts of borosilicate modified plant-based phenolic epoxy resin are mixed and stirred. Then, 5 parts of polyamide curing agent, 1.4 parts of accelerator 2-ethyl-4-methylimidazolium, 1.5 parts of magnesium stearate and 1.7 parts of silane coupling agent KH-562 are added and heated and stirred. First, the mixture is stirred at 106℃ for 70 min, and then at 118℃ for 110 min. After cooling, the mixture is crushed and sieved to obtain coated recycled sand for casting.
[0040] Preparation of the borosilicate-modified plant-based phenolic epoxy resin: 125 parts by weight of guaiacol and 64 parts by weight of 37% formaldehyde solution were added to a reaction vessel, followed by the dropwise addition of 5 parts by weight of 40% hydrochloric acid and stirring for 24 minutes. The mixture was then heated to 78°C and reacted for 9 hours. After standing and separating into layers, the lower oily liquid was collected and washed with deionized water, followed by rotary evaporation to obtain the plant-based phenolic resin. Under a nitrogen atmosphere, 9 parts by weight of the plant-based phenolic resin and 98 parts by weight of epichlorohydrin were added to a reaction vessel and stirred for 54 minutes. Then, 1.5 parts by weight of benzyltriethylammonium chloride were added and reacted at 68°C for 4 hours. Next, 9 parts by weight of 40% sodium hydroxide aqueous solution were added and reacted at 78°C for 70 minutes. After the reaction was complete, the mixture was filtered, the filtrate was collected and extracted, the lower oily liquid was separated, and the mixture was rotary evaporated to obtain the final product. To obtain plant-based phenolic epoxy resin: 45 parts of phenyltriethoxysilane, 11 parts of dimethyldiethoxysilane, and 3 parts of boric acid were added to 87 parts of anhydrous ethanol, followed by the addition of 1.3 parts of 1 mol / L hydrochloric acid solution and heating to 64℃ with stirring for 110 min. The mixture was then rotary evaporated, washed with water, and dried to obtain a borosilicate compound. In a reaction vessel, 42 parts of anhydrous ethanol and 8 parts of deionized water were mixed, and 1.5 parts of 3-aminopropyltriethoxysilane were added and stirred at 60℃ for 180 min. Then, 16 parts of the borosilicate compound were added and stirred for 34 min. Finally, 37 parts of plant-based phenolic epoxy resin were added and stirred for 55 min. The mixture was heated to 90℃ and 0.5 parts of dibutyltin dilaurate were added for modification treatment for 7 h. The mixture was then cooled to room temperature, washed with water, and dried to obtain borosilicate-modified plant-based phenolic epoxy resin.
[0041] Comparative Example 1 The difference between this comparative example and Example 1 is that carbon-containing calcined sand is used instead of recycled sand.
[0042] Comparative Example 2 The difference between this comparative example and Example 1 is that ordinary phenolic epoxy resin (model F-51) is used instead of borosilicate modified plant-based phenolic epoxy resin.
[0043] Comparative Example 3 The difference between this comparative example and Example 1 is that plant-based phenolic epoxy resin is used instead of borosilicate-modified plant-based phenolic epoxy resin.
[0044] Performance testing The room temperature flexural strength, hot flexural strength, and loss on ignition of the above-mentioned examples and comparative examples were tested in accordance with the requirements of "JB / T 8583-2008 Coated Sand for Foundry".
[0045] The performance test data above are shown in Table 1.
[0046] Table 1 Performance Test Results Example 1 9.71 4.93 1.87 Example 2 9.58 4.86 1.93 Example 3 9.65 4.89 1.91 Comparative Example 1 5.09 2.41 4.25 Comparative Example 2 5.83 2.97 3.72 Comparative Example 3 7.76 3.82 2.69 As can be seen from the above, the present invention first activates waste phenolic resin casting sand to obtain carbon-containing calcined sand, then impregnates the carbon-containing calcined sand to obtain recycled sand, and simultaneously prepares plant-based phenolic resin using guaiacol and formaldehyde as raw materials, and obtains borosilicate-modified plant-based phenolic epoxy resin through epoxidation and modification treatment, and finally mixes the recycled sand, borosilicate-modified plant-based phenolic epoxy resin, polyamide curing agent, accelerator, magnesium stearate and coupling agent to obtain coated recycled sand for casting (Examples 1 to 3), which has the best comprehensive performance.
[0047] Compared to Example 1, the use of calcined carbon-containing sand instead of recycled sand, and the lack of impregnation treatment with mannitol aqueous solution, resulted in a decrease in flexural strength and an increase in loss on ignition (Comparative Example 1); compared to Example 1, the use of ordinary phenolic epoxy resin (model F-51) instead of borosilicate-modified plant-based phenolic epoxy resin, and the lack of the effect of borosilicate-modified plant-based phenolic epoxy resin, resulted in a decrease in flexural strength and an increase in loss on ignition (Comparative Example 2); compared to Example 1, the use of plant-based phenolic epoxy resin instead of borosilicate-modified plant-based phenolic epoxy resin, and the lack of the effect of borosilicate compounds, resulted in a decrease in flexural strength and an increase in loss on ignition (Comparative Example 3).
Claims
1. A method for recycling waste foundry sand, characterized in that, Includes the following steps: S1. First, the waste phenolic resin casting sand is activated to obtain carbon-containing calcined sand, and then the carbon-containing calcined sand is impregnated to obtain recycled sand. S2. Stir and mix the recycled sand and phenolic epoxy resin described in step S1, then add polyamide curing agent, accelerator, magnesium stearate and coupling agent, heat and stir, cool, crush and sieve to obtain coated recycled sand for casting.
2. The method for recycling waste foundry sand according to claim 1, characterized in that, The components in step S2, by weight, include: 80-90 parts recycled sand, 8-12 parts phenolic epoxy resin, 4-6 parts polyamide curing agent, 1-2 parts accelerator, 1-2 parts magnesium stearate, and 1-2 parts coupling agent.
3. The method for recycling waste foundry sand according to claim 1, characterized in that, The activation process described in step S1 is as follows: place the waste phenolic resin casting sand in a vertical activation furnace, control the steam flow rate to be 10~20mL / min, and activate it at 840~860℃ for 120~140min to obtain carbon-containing calcined sand.
4. The method for recycling waste foundry sand according to claim 1, characterized in that, The impregnation process described in step S1 is as follows: by weight, 80-90 parts of carbon-containing calcined sand are impregnated in 900-1000 parts of 1mol / L mannitol aqueous solution, impregnated at 30-40℃ for 20-24 hours, filtered, washed with water, and dried to obtain regenerated sand.
5. The method for recycling waste foundry sand according to claim 1, characterized in that, The phenolic epoxy resin is a borosilicate modified plant-based phenolic epoxy resin. The preparation method of the borosilicate-modified plant-based phenolic epoxy resin is as follows: first, plant-based phenolic resin is prepared using guaiacol and formaldehyde as raw materials; then, the plant-based phenolic resin is epoxidized using epichlorohydrin to obtain plant-based phenolic epoxy resin; finally, the plant-based phenolic epoxy resin is modified using borosilicate compounds to obtain borosilicate-modified plant-based phenolic epoxy resin.
6. The method for recycling waste foundry sand according to claim 5, characterized in that, The preparation steps of the plant-based phenolic resin are as follows: by weight, 120-130 parts of guaiacol and 62-68 parts of 37% formaldehyde solution are added to the reaction vessel, then 4-6 parts of 40% hydrochloric acid are added dropwise and stirred for 20-30 minutes. The temperature is raised to 70-80℃ and reacted for 8-10 hours. After standing and separating into layers, the lower oily liquid is collected and washed with deionized water. The mixture is then rotary evaporated to obtain the plant-based phenolic resin.
7. The method for recycling waste foundry sand according to claim 5, characterized in that, The preparation steps of the plant-based phenolic epoxy resin are as follows: by weight, 8-12 parts of plant-based phenolic resin and 90-100 parts of epichlorohydrin are added to a reaction vessel under a nitrogen atmosphere and stirred for 50-60 minutes. Then, 1-2 parts of benzyltriethylammonium chloride are added and reacted at 65-70°C for 3-5 hours. Then, 8-10 parts of 40% sodium hydroxide aqueous solution are added and reacted at 75-80°C for 60-80 minutes. After the reaction is completed, the mixture is filtered, the filtrate is collected and extracted, the lower oily liquid is separated, and the mixture is rotary evaporated to obtain the plant-based phenolic epoxy resin.
8. The method for recycling waste foundry sand according to claim 5, characterized in that, The modification process is as follows: by weight, 40-45 parts of anhydrous ethanol and 5-10 parts of deionized water are mixed in a reactor, and then 1-2 parts of 3-aminopropyltriethoxysilane are added and stirred at 60°C for 150-250 min. Then, 10-20 parts of borosilicate compound are added and stirred for 30-40 min. Next, 30-40 parts of plant-based phenolic epoxy resin are added and stirred for 50-60 min. After heating to 90°C, 0.4-0.6 parts of dibutyltin dilaurate are added for modification treatment for 6-8 h. After cooling to room temperature, the mixture is washed with water and dried to obtain borosilicate-modified plant-based phenolic epoxy resin.
9. A method for recycling waste foundry sand according to claim 8, characterized in that, The preparation steps of the borosilicate compound are as follows: by weight, 40-50 parts of phenyltriethoxysilane, 10-12 parts of dimethyldiethoxysilane and 2-4 parts of boric acid are added to 80-90 parts of anhydrous ethanol, then 1-2 parts of 1mol / L hydrochloric acid solution are added and the mixture is heated to 60-70℃ and stirred for 100-120 min. The mixture is then rotary evaporated, washed with water, and dried to obtain the borosilicate compound.
10. A method for recycling waste foundry sand according to claim 1, characterized in that, The accelerator is selected from one or more of N,N-dimethylbenzylamine, 2-methylimidazole, and 2-ethyl-4-methylimidazole.